Pendampingan Pil Cantik dan Pisang Ambon pada Remaja Putri - Maiyo, Ferniyani; Sarapang, Divya; Djafar, Vivi Oktaviani; Khasanah Nggilu, Siti Uswatun (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2023)
Anemia is a nutritional problem with a high prevalence compared to other malnutrition problems. Ambon bananas contain vitamin C and iron levels, to increase iron absorption in the body. Teenage girls need to take Fe tablets because every month they have menstruation. The purpose of this community service activity is to provide education, demonstrations, to young women so that they can understand about beautiful pills (Fe tablets) and how to process Ambon banana juice to increase hemoglobin levels. Activity Methods namely; (1) Collecting the target of young women as many as 50 respondents; (2) pre Hb examination; (3) Conduct a pre test regarding the level of knowledge about anemia; (4) Counseling on anemia; (5) Distribution of Fe tablets; (6) Distribution of Ambon bananas to young women; (7) Conducting post test questionnaire; (8) Fe examination post test. The results achieved before giving counseling A total of 41 people (82%) of 50 young women with good knowledge, then good knowledge increased to 50 people (100%) after giving counseling. The results of the Hb examination in adolescent girls found normal categories of 30 people, mild anemia 17 people and moderate anemia 3 people. After being given beautiful pills and Ambon bananas to young women, the results of the Hb examination increased, namely hemoglobin levels in the normal category as many as 38 people and mild anemia as many as 12 people.